Evaluation of the suitability of the parthenogenetic marbled crayfish for aquaculture: potential benefits versus conservation concerns - Vogt, Günter (Hydrobiologia, 2021)
The parthenogenetic marbled crayfish, Procambarus virginalis, is currently being discussed as a promising new candidate for aquaculture that could supply people in developing countries with high-quality protein and income. The main advantage of marbled crayfish is parthenogenetic reproduction. Comparison of growth between marbled crayfish and red swamp crayfish, Procambarus clarkii, the leading species in crayfish aquaculture revealed inferior body size and considerably slower growth in marbled crayfish. Only a very small proportion of the production would meet the size requirement of the international market and could serve as a cash crop. Aquaculture for local markets in extensive outdoor systems is probably economically feasible in developing countries, but the highly invasive and competitive marbled crayfish could easily escape from such sites, invade natural ecosystems and impair the autochthonous fauna and flora. Culture in closed indoor systems would be a safe alternative but this cost-intensive approach is economically not profitable. Because of small body size and slow growth, conservation concerns, and economic reasons, the marbled crayfish is considered unsuitable for aquaculture. It should not be spread around the globe for aquaculture and sustainable fisheries as was earlier done with the congeneric Procambarus clarkii, resulting in devastating ecological effects in numerous countries.